Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Proyek Konstruksi: Studi Komparatif di Empat Lokasi di Sumatera - J. EL- Matury, Herlina; Syahlan, Nabila; Baharuddin, Mohd Rafee B.; Ginting, Evfy Septriani BR; Inggrianingsi, Inggrianingsi; Batubara, Saiful (Universitas Hang Tuah Pekanbaru, 2025)
The Occupational Safety and Health Management System (OSH-MS) is a critical framework for promoting safe working environments, particularly within infrastructure construction projects characterized by high risk and extensive labor involvement. Despite its regulatory importance, OSH-MS implementation remains inconsistent across projects, influenced by managerial capacity, technical complexity, and contextual factors. This descriptive quantitative study evaluated the implementation of OSH-MS in four infrastructure projects: the LS Dam Project, the KAPB Toll Bridge Project, the Old Town (Kesawan) Project, and the Waste Drainage Project. The assessment was based on five OSH-MS principles policy establishment, planning, implementation, monitoring and evaluation, and performance review supported by twelve operational elements. Data were collected using structured checklists and compliance scoring, analyzed descriptively, and presented through tables and charts. The Old Town Project (93%) and KAPB Toll Bridge Project (87%) demonstrated strong OSH-MS implementation, classified as “good,” while the LS Dam (71%) and Waste Drainage (73%) projects exhibited moderate compliance, categorized as “fair.” Weaknesses were primarily found in document control, inspection procedures, and performance monitoring, particularly in larger, multi-contractor projects. The findings reveal uneven OSH-MS maturity across projects, emphasizing the need for stronger national and local policy enforcement, routine audits, and continuous workforce training. Consistent implementation of OSH-MS not only enhances safety and project efficiency but also supports worker health and contributes to Sustainable Development Goal 8 on decent work and economic growth.